The Routledge Companion To World History Since 1914. - Cook, Dr Chris (Taylor & Francis Ltd., 2005)
This is an outstanding compendium of facts and figures on World History. Fully up-to-date, reliable and clear, this volume is the indispensable and user-friendly source of information on a thorough range of topics.